Pharmacodynamics of daptomycin and vancomycin on Enterococcus faecalis and Staphylococcus aureus demonstrated by studies of initial killing and postantibiotic effect and influence of Ca2+ and albumin on these drugs. - Hanberger, H (1991)
The pharmacodynamics of daptomycin and vancomycin on Enterococcus faecalis ATCC 29212 and Staphylococcus aureus ATCC 25923 were investigated by studying the postantibiotic effect (PAE) and initial killing. The influence of Ca2+ and albumin on these drugs was also evaluated. The PAE was studied by use of bioluminescence assay of bacterial ATP. Daptomycin at clinically achievable concentrations produced a dose-dependent PAE on E. faecalis (0.6 to 6.7 h) and S. aureus (1.0 to 6.3 h). The long PAE of daptomycin was seen simultaneously with a potent dose-dependent initial killing assayed by viable count determination. The initial change in bacterial ATP was not as extensive as the decrease in viability. Vancomycin at corresponding concentrations produced shorter PAEs on E. faecalis (0.5 to 1.0 h) and S. aureus (1.3 to 1.8 h). This coincides with a weak non-dose-dependent initial change in viability and intracellular ATP. The MICs of vancomycin were not influenced by different Ca2+ concentrations or by the addition of albumin to the broth. The MICs of daptomycin for both strains were lowered, and the PAEs were prolonged with increasing concentrations of Ca2+ in the broth. The PAE of daptomycin was Ca2+ dependent to the same extent as the MIC was. In the presence of physiological concentrations of albumin and free Ca2+, the PAEs of daptomycin on both strains were reduced and the MICs were increased in comparison with the results obtained in pure Mueller-Hinton broth with approximately the same free Ca2+ concentration. This decrease in daptomycin activity was considered to be due to the albumin binding of daptomycin. Despite the albumin binding of daptomycin, the PAE produced on E. faecalis and S. aureus in the presence of a physiological free Ca2+ concentration was still over 6 h at clinically achievable concentrations.